Characterization of a microwave frequency resonator via a nearby quantum dot - Frey, T; Leek, P; Beck, M; Ensslin, K; Wallraff, A; Ihn, T (2011)
We present measurements of a hybrid system consisting of a microwave transmission-line resonator and a lateral quantum dot defined on a GaAs heterostructure. The two subsystems are separately characterized and their interaction is studied by monitoring the electrical conductance through the quantum dot. The presence of a strong microwave field in the resonator is found to reduce the resonant conductance through the quantum dot and is attributed to electron heating and modulation of the dot potential. We use this interaction to demonstrate a measurement of the resonator transmission spectrum using the quantum dot. © 2011 American Institute of Physics.